2007
DOI: 10.1590/s1980-57642008dn10200006
|View full text |Cite
|
Sign up to set email alerts
|

Working memory: Differences between young adults and the aged in listening tasks *

Abstract: Working memory is a system with a limited capacity which enables the temporary storage and manipulation of the information necessary for complex cognitive tasks. Numerous studies have suggested that performance in these tasks is related to age where older adults have a lesser performance than the young.ObjectiveTo analyze the processing functions of working memory in a listening task.Method59 educated participants aged between 19 and 76 years having no memory complaints were divided into two groups (young and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Working memory, like other cognitive abilities declines with age, however, some specific diseases, such as AUD, can decrease an individual's WM capacity, even in a young population [4]. In an experiment examining the effect of age on working memory, researchers divided 59 participants between 19 and 76 years into two groups (young and aged adults).…”
Section: Behavioral Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Working memory, like other cognitive abilities declines with age, however, some specific diseases, such as AUD, can decrease an individual's WM capacity, even in a young population [4]. In an experiment examining the effect of age on working memory, researchers divided 59 participants between 19 and 76 years into two groups (young and aged adults).…”
Section: Behavioral Deficitsmentioning
confidence: 99%
“…Simultaneously, participants needed to store the last word of each sentence for later recall. It was found that older adults have a much harder time remembering words than younger people, which makes sense since WM gets worse with age [4].…”
Section: Behavioral Deficitsmentioning
confidence: 99%
“…Also, a large number of studies have shown that the difference between younger and older people's performance is more accentuated with the increase in WM demands (e.g. updating information, inhibiting of task-irrelevant stimuli, shifting mental sets; Dorbath et al, 2011;Freitas et al, 2007;Oberauer, 2001;Yi & Friedman, 2015). These findings converge with functional magnetic resonance imaging (fMRI) studies showing bilateral activation of WM-related prefrontal areas in older adults, which may compensate for cognitive decline and to maintain performance in WM tasks at higher levels of complexity (Reuter-Lorenz et al, 2005), suggesting that WM is especially sensitive to age-related changes.…”
Section: The Role Of Working Memory Trainingmentioning
confidence: 99%
“…Therefore, the age of young adults will provide proof regarding their ability to identify their understanding of Lanna architecture through words, images, sounds, etc. In addition, Freitas, M. I. d'Ávila et al (2007) assert that the three subcomponents of working memory have a significant role in controlling attention and coordinating activity in young adults. Moreover, this current study involves different activities set out to test the ability of young adults as concerns their knowledge of Lanna architecture.…”
Section: Literature Review Working Memorymentioning
confidence: 99%